Parental Internet Use and Health Information Seeking Behavior Comparing Elective and Emergency Pediatric Surgical Situations - Wong, Michael Kien Yee; Sivasegaran, Daveraj; Choo, Candy Suet Cheng; Nah, Shireen Anne (European Journal of Pediatric Surgery, 2018)
Introduction This study evaluates usage patterns of online health information in parents with children undergoing elective or emergency surgical procedures.Materials and Methods We prospectively surveyed parents of children admitted to our institution for common emergency (appendicectomy, abscess drainage, gonadal torsion) or elective (herniotomy, orchidopexy) operations between March and September 2016. Each completed an anonymized modification of a previously published survey comprising 19 questions on demographic data, Internet usage, and review of Internet resources. Chi-square tests were used for categorical data with p < 0.05 considered significant.Results Eighty-four parents were surveyed: 50(59.5%) elective and 34(40.5%) emergency procedures, with no refusals. Majority were mothers (n = 53; 63.1%). Despite high home Internet availability (n = 81; 96.4%) and high casual Internet usage rates (74 parents, 88.1%, reported daily use), just 38 (76%) parents from the elective group and 24 (70.6%) from the emergency group went online to access their child's admitting condition. Friends and family were more likely to be approached for information in elective (n = 27; 54%) and emergency groups (n = 24;70.6%) than general practitioners or other health care workers. When condition-specific online information was sought, more than 95% felt that the information concurred with the doctor's. Most common reasons were for more information on the condition (n = 56; 90.3%) and on medical treatment (n = 52; 83.9%). Eighteen (18/62; 29%) parents reported excessively technical information. No significant difference in behavior was found comparing elective and emergency groups.Conclusion Approximately one quarter of parents do not access condition-specific online medical information despite high Internet penetration rates. More than half depend on friends and family for additional information, reflecting societal and cultural norms in our population. Surgeons must incorporate awareness of these behaviors during counselling
Keywords: caregiver; children; self-report